Fluoride complexation by bidentate silicon Lewis acids. Issue 6 (20th January 2017) - Horstmann, Jan; Niemann, Mark; Berthold, Katarína; Mix, Andreas; Neumann, Beate; Stammler, Hans-Georg; Mitzel, Norbert W.
Abstract : The fluoride ion complexation behavior of the bidentate open-chain Lewis acids Ph2 Si(CHCHSiF n Me3− n )2 and Ph2 Si(CH2 –CH2 SiF n Me3− n )2 ( n = 1, 2, 3) was explored in detail by multinuclear low-temperature NMR spectroscopy in solution and by X-ray diffraction experiments. Abstract : Diethynyldiphenylsilane (1 ) and divinyldiphenylsilane (2 ) were functionalized by hydrosilylation reactions with HSiMe2 Cl, HSiMeCl2 and HSiCl3 . Fluorination of the resulting compounds generates bidentate open-chain Lewis acids of increasing acidity. All semi-flexible [Ph2 Si(CHCHSiF n Me3− n )2 ( n = 1, 2, 3)] and flexible [Ph2 Si(CH2 –CH2 SiF n Me3− n )2 ( n = 1, 2, 3)] bidentate Lewis acids were obtained in good to excellent yields. The different fluoride ion complexation behavior was explored in detail by multinuclear (low temperature) NMR spectroscopy. The Lewis acidic bidentate molecules as well as the resulting mono- and bissilicates were completely characterized by NMR spectroscopy, mass spectrometry and in part by elemental analysis and X-ray diffraction experiments.